"A Step and a Ceiling": mechanical properties of Ca2+ spark vasoregulation in resistance arteries by pressure‐induced oxidative activation of PKG. Issue 22 (28th November 2019) - Csato, Viktoria; Kadir, Sharifah Z. S. A.; Khavandi, Kaivan; Bennett, Hayley; Sugden, Sarah; Gurney, Alison M.; Pritchard, Harry A. T.; Hill‐Eubanks, David; Eaton, Philip; Nelson, Mark T.; Greenstein, Adam S.
Abstract: We investigated the biomechanical relationship between intraluminal pressure within small mesenteric resistance arteries, oxidant activation of PKG, Ca 2+ sparks, and BK channel vasoregulation. Mesenteric resistance arteries from wild type (WT) and genetically modified mice with PKG resistance to oxidative activation were studied using wire and pressure myography. Ca 2+ sparks and Ca 2+ transients within vascular smooth muscle cells of intact arteries were characterized using high‐speed confocal microscopy of intact arteries. Arteries were studied under conditions of varying intraluminal pressure and oxidation. Intraluminal pressure specifically, rather than the generic stretch of the artery, was necessary to activate the oxidative pathway. We demonstrated a graded step activation profile for the generation of Ca 2+ sparks and also a functional "ceiling" for this pressure –‐sensitive oxidative pathway. During steady state pressure ‐ induced constriction, any additional Ca 2+ sensitive‐K + channel functional availability was independent of oxidant activated PKG. There was an increase in the amplitude, but not the Area under the Curve (AUC) of the caffeine‐induced Ca 2+ transient in pressurized arteries from mice with oxidant‐resistant PKG compared with wild type. Overall, we surmise that intraluminal pressure within resistance arteries controls Ca 2+ spark vasoregulation through a tightly controlled pathway with a graded onset switch. The pathway, underpinned by oxidant activation of PKG, cannot be further boosted by additional pressure or oxidation once active. We propose that these restrictive characteristics of pressure‐induced Ca 2+ spark vasoregulation confer stability for the artery in order to provide a constant flow independent of additional pressure fluctuations or exogenous oxidants. Abstract : Intraluminal pressure within resistance arteries triggers a binary activation of an oxidant‐driven pathway whereby protein kinase G regulates calcium spark vasoregulation. Once activated, the pathway cannot be boosted by additional pressure or oxidants and we propose this confers stability upon the pressure‐induced constriction of the artery.